The legal regime of the public officer’s right to casual leaveto establish an enterprise according to Law No 22-22 and its regulatory text - debbih, adel (The journal of Teacher Researcher of Legal and political Studies, 2024)
The Law No. 22-22 includes the addition of eight new articles to Ordinance 06-03, starting from Article 206 bis to Article 206 bis 7 It introduces a new functional right for public officer’s that allows them to establish an enterprise under specific legal conditions and regulations, detailing the conditions and procedures for public officers to benefit from this leave and outlining the consequences thereof Executive Decree No. 23-93, dated March 5, 2023, was issued, whereby public officers belonging to certain categories, who have at least five years of service and are under 55 years of age, may submit a request to benefit from the casual leave for business establishment, This request is being subjected to review by the administration, which may approve it, postpone its approval, or reject it for reasons administration interest. In the event that the public officers request is accepted, the functional relationship is suspended for one year, extendable for an additional six months, The public officer has the right to reintegrate into their position upon his request incase the nonsuccess of the business project , and the functional relationship may terminate incase of the business project's success. Keywords: public officer, casual leave, establish an enterprise